2006
DOI: 10.1007/s00726-005-0302-x
|View full text |Cite
|
Sign up to set email alerts
|

A combination of caffeine and taurine has no effect on short term memory but induces changes in heart rate and mean arterial blood pressure

Abstract: Red Bull energy drink has become extraordinarily popular amongst college students for use as a study aid. We investigated the combined effects of Red Bull's two active ingredients, caffeine and taurine, on short term memory. Studies on the effects of these two neuromodulators on memory have yielded mixed results, and their combined actions have not yet been investigated. In this double-blind study, college student subjects consumed either caffeine and taurine pills or a placebo and then completed a memory asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 22 publications
6
63
1
6
Order By: Relevance
“…In one such study (28), the ingestion of capsules containing 100 mg caffeine and 1000 mg taurine did not alter mean arterial blood pressure at 45 min postconsumption, but increased blood pressure after subjects underwent a memory test at 70 min postconsumption. In another study that compared the impact of 500 mL Red Bull ED with or without taurine on heart rate and stroke volume before and after exercise, Baum and Weiss (26) showed that the ED led to significant increases in the contractility of the left atrium during a postexercise recovery period.…”
Section: Impact Of Taurinementioning
confidence: 98%
“…In one such study (28), the ingestion of capsules containing 100 mg caffeine and 1000 mg taurine did not alter mean arterial blood pressure at 45 min postconsumption, but increased blood pressure after subjects underwent a memory test at 70 min postconsumption. In another study that compared the impact of 500 mL Red Bull ED with or without taurine on heart rate and stroke volume before and after exercise, Baum and Weiss (26) showed that the ED led to significant increases in the contractility of the left atrium during a postexercise recovery period.…”
Section: Impact Of Taurinementioning
confidence: 98%
“…A dose of caffeine 85-250 mg may result in feelings of alertness, decreased fatigue, and eased flow of thought. Whereas, excessive caffeine uses 250-500mgresulted in restlessness, nervousness, insomnia, tremors, seizures and cardiovascular instability [11][12][13][14][15], in addition, it leads to hypokalemia [16,17]. With the rising popularity of energy drinks and with more young people ingesting higher levels of caffeine, more serious health problems are now being reported.…”
Section: Introductionmentioning
confidence: 99%
“…Despite accumulation of findings on the relationship between taurine and synaptic plasticity by electrophysiological studies, the effect of taurine on learning and memory at the behavior level is complicated. Studies of acute administration of taurine indicate that it has no effect on humans [1,20] and mice [15], whereas studies investigating the subacute or chronic effect of taurine, often taken exogenously in food supplements on a daily basis, are still controversial. Sanberg and Fibiger reported that taurine impaired memory functions [16].…”
mentioning
confidence: 99%